Effect of Prunus Amagdalis (Almonds) on testosterone in Atenolol-induced derangements in the hormonal profile of male Balb-c mice - Irum Rehman, Faizania Shabbir, Maria Gill, Shahid Hameed, Amna Rasul, Attiqa Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Infertility is a very common health problem among middle-aged hypertensive individuals on beta-blocker therapy. With advancing research, it is observed that almonds can enhance the fertility index. Aim: To find that how almonds (prunus Amygdalus), cardioselective beta blocker and combined preparation of both these can affect serum testosteronein mice. Methods: This study was done in the Physiology Department, Shifa College of Medicine, Islamabad. Some part of this project was done inNational Institute of Health, Islamabad along with the Centre for Research in Experimental and Applied Medicine (CREAM) Laboratory, Army Medical College, Rawalpindi, and Shifa International Hospital, Islamabad. It was an Animal based experimental study. This study was conducted from December2014 to March 2015. 120 Balb-c mice were selected for our study according to the predefined setcriteria and four groups were made, each group consisting of 30 mice. Group A was the control group, atenolol was given to group B, almonds to group C, and atenolol plus almonds to group D. Serumtestosterone was measured after 3 months. Data was analyzed using SPSS version 17 and mean±standard deviation was determined. For difference, statistical significance was calculated after applying one way ANOVA. The p-value < 0.05 was considered significant. Results: In group A serving as control mean testosterone was found to be 1.58±0.69IU/L. Mean serum testosterone in B-group (Atenolol) was 0.43±0.27 IU/L. In group C (Almonds) it was 3.77±2.64 IU/Lwhich was significantly increased. In group D (almond+Atenolol) serum testosterone level was1.82±1.00 IU/L that is elevated but non-significantly in comparison to the control group. Conclusion: Almonds increase mean testosterone and atenolol lead to adecrease init. It is thus concluded that almondscan revert the changes induced by atenolol. Keywords: Almonds, Testosterone, Atenolol, Hypertension, Infertility.